Luminescent Aptamer-Based Bioassays for Sensitive Detection of Food Allergens - Donato Calabria; Martina Zangheri; Seyedeh Rojin Shariati Pour; Ilaria Trozzi; Andrea Pace; Elisa Lazzarini; Maria Maddalena Calabretta; Mara Mirasoli; Massimo Guardigli (Biosensors, 2022)
The presence of hidden allergens in food products, often due to unintended contamination along the food supply chain (production, transformation, processing, and transport), has raised the urgent need for rapid and reliable analytical methods for detecting trace levels of such species in food products. Indeed, food allergens represent a high-risk factor for allergic subjects due to potentially life-threatening adverse reactions. Portable biosensors based on immunoassays have already been developed as rapid, sensitive, selective, and low-cost analytical platforms that can replace analyses with traditional bench-top instrumentation. Recently, aptamers have attracted great interest as alternative biorecognition molecules for bioassays, since they can bind a variety of targets with high specificity and selectivity, and they enable the development of assays exploiting a variety of transduction and detection technologies. In particular, aptasensors based on luminescence detection have been proposed, taking advantage of the development of ultrasensitive tracers and enhancers. This review aims to summarize and discuss recent efforts in the field of food allergen analysis using aptamer-based bioassays with luminescence detection.